Current therapies and progress in the treatment of advanced gastric cancer - Li, Hongyu; Shen, Ming; Wang, Shihao (Frontiers in Oncology, 2024)
Gastric cancer (GC) remains one of the most life-threatening disease worldwide with poor prognosis because of the absence of effective treatment and the delay in diagnosis. Due to the delay of diagnosis, a large proportion of GC patients are diagnosed as advanced GC, with extreme short lifespan. In the past few years, some pivotal progress and novel therapies was proposed, and conducted into clinical researches and practice. In this study, we summarized the development of several novel immunotherapy or targeted treatment modalities for advanced GC, including immune checkpoint inhibitors, anti-angiogenic therapy and cancer vaccines. Additionally, the advantage and potential weakness in each of these therapeutic methods are also listed. Finally, we discussed the promising research direction of advanced GC treatment, and the limitation in basic and clinical research of advanced GC, including the combination of immunotherapy and targeted therapy.